Leveraging ICT for Integrating Regulatory Functions for Cross-Border Trade: Development of Pakistan Single-Window Platform - Shah, Syed Shakeel (Journal of Pakistan Administration, 2021)
Cross-border trade plays a key role in the economic activity of every country. Import and export of goods through Pakistan’s borders involve a complex regulatory regime involving a large number of departments/entities which are entrusted with compliance functions through a system of licenses, permits, certificates, NoCs, etc. The legacy manual system comprising fragmented regulatory compliance of different government agencies used to cause delays at border nodes, added transactional costs and adversely impacted competitiveness of businesses. Consequently, Pakistan’s rankings in international indexes measuring efficiency of trade regulation functions were also affected. These showed a continuous decline over a long period, as other countries improved their trade governance systems leveraging the tremendous potential of information and communication technologies (ICT) for development of National Single Window (NSW).